HIV testing and willingness to get HIV testing at a peer-run drop-in centre for people who inject drugs in Bangkok, Thailand - Ti Lianping; Hayashi Kanna; Kaplan Karyn; Suwannawong Paisan; Fu Eric; Wood Evan; Kerr Thomas (BMC, 2012)
Abstract Background Regular HIV testing among people who inject drugs is an essential component of HIV prevention and treatment efforts. We explored HIV testing behaviour among a community-recruited sample of injection drug users (IDU) in Bangkok, Thailand. Methods Data collected through the Mitsampan Community Research Project were used to examine correlates of HIV testing behaviour among IDU and to explore reasons for not being tested. Multivariate logistic regression was used to examine factors associated with willingness to access HIV testing at the drug-user-run Mitsampan Harm Reduction Centre (MSHRC). Results Among the 244 IDU who participated in this study, 186 (76.2%) reported receiving HIV testing in the previous six months. Enrolment in voluntary drug treatment (odds ratio [OR] = 2.34; 95% confidence interval [CI]: 1.18 - 4.63) and the tenofovir trial (OR = 44.81; 95%CI: 13.44 - 149.45) were positively associated with having been tested, whereas MSHRC use (OR = 1.78; 95%CI: 0.96 - 3.29) was marginally associated with having been tested. 56.9% of those who had not been tested reported in engaging in HIV risk behaviour in the past six months. 181 (74.2%) participants were willing to be tested at the MSHRC if testing were offered there. In multivariate analyses, willingness to get HIV testing at the MSHRC was positively associated with ever having been to the MSHRC (adjusted odds ratio [AOR] = 2.42; 95%CI: 1.21 - 4.85) and, among females, being enrolled in voluntary drug treatment services (AOR = 9.38; 95%CI: 1.14 - 76.98). Conclusions More than three-quarters of IDU received HIV testing in the previous six months. However, HIV risk behaviour was common among those who had not been tested. Additionally, 74.2% of participants were willing to receive HIV testing at the MSHRC. These findings provide evidence for ongoing HIV prevention education, as well potential benefits of incorporating HIV testing for IDU within peer-led harm reduction programs.